2021
DOI: 10.3390/w13030350
|View full text |Cite
|
Sign up to set email alerts
|

Start-Up of Anammox SBR from Non-Specific Inoculum and Process Acceleration Methods by Hydrazine

Abstract: Biological nutrient removal from wastewater to reach acceptable levels is needed to protect water resources and avoid eutrophication. The start-up of an anaerobic ammonium oxidation (anammox) process from scratch was investigated in a 20 L sequence batch reactor (SBR) inoculated with a mixture of aerobic and anaerobic sludge at 30 ± 0.5 °C with a hydraulic retention time (HRT) of 2–3 days. The use of NH4Cl, NaNO2, and reject water as nitrogen sources created different salinity periods, in which the anammox pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 63 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Shah, Ali et al [21] and Tanaka, Fujimoto et al ( 2008) [22] proposed that a hybrid methodology comprised of coagulation and adsorption was a more cost effective, environ-mentally friendly, and optimized treatment. Earlier, several studies have shown biological nutrient removal possibilities [23][24][25][26][27][28][29][30] studied the removal of nutrients from wastewater by using polyethylene biofilm carriers as well as studies on adsorption of hazardous dyes [31][32][33].…”
Section: Selection Of Bacterial Strainsmentioning
confidence: 99%
“…Shah, Ali et al [21] and Tanaka, Fujimoto et al ( 2008) [22] proposed that a hybrid methodology comprised of coagulation and adsorption was a more cost effective, environ-mentally friendly, and optimized treatment. Earlier, several studies have shown biological nutrient removal possibilities [23][24][25][26][27][28][29][30] studied the removal of nutrients from wastewater by using polyethylene biofilm carriers as well as studies on adsorption of hazardous dyes [31][32][33].…”
Section: Selection Of Bacterial Strainsmentioning
confidence: 99%
“…For example, Tetracyclines were eliminated to a higher extent at 55 °C than at 22 °C and 38 °C within compost treatments [ 31 ]. However, further research on its mechanism requires more experiments in sterile reactors because microbes are often important indicators of the process of aerobic and anaerobic reactions [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of anammox by Mulder [ 8 ] in 1995, extensive research has been carried out to develop anammox-driven nitrogen removal technologies. Considering the limitations of the conventional wastewater treatment systems, the combination of biological processes such as in the sequencing batch reactor (SBR) stands as a promising and viable option for sewage treatment, with low cost, high efficiency, and high stability [ 9 , 10 , 11 ]. Additionally, the partial nitrification/anammox process (PNA) provides an effective new option for the treatment of high-strength NH 4 + wastewater with a low C/N ratio and elevated temperature.…”
Section: Introductionmentioning
confidence: 99%